2012
DOI: 10.1097/mpa.0b013e318221c4a8
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Early Enteral Feeding Through Nasogastric and Nasojejunal Tube in Severe Acute Pancreatitis

Abstract: Early enteral feeding through NG was not inferior to NJ in patients with SAP. Infectious complications were within the noninferiority limit. Pain in refeeding, intestinal permeability, and endotoxemia were comparable in both groups.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
131
0
8

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 141 publications
(140 citation statements)
references
References 29 publications
1
131
0
8
Order By: Relevance
“…A recent non inferiority trial of 78 patients randomized to nasogastric or radiologicallyconfirmed nasojejunal feeding was recently published, showing noninferiority of nasogastric feeds. However, there was a higher rate of infectious complications, need for surgical intervention for infected necrosis, and mortality in the nasogastric feeding group [13] . A prospective, randomized controlled trial evaluating nasogastric vs nasojejunal feeding called the Study on Nutrition in Acute Pancreatitis is currently underway, which will provide further evi dence on this subject.…”
Section: Feedingmentioning
confidence: 99%
“…A recent non inferiority trial of 78 patients randomized to nasogastric or radiologicallyconfirmed nasojejunal feeding was recently published, showing noninferiority of nasogastric feeds. However, there was a higher rate of infectious complications, need for surgical intervention for infected necrosis, and mortality in the nasogastric feeding group [13] . A prospective, randomized controlled trial evaluating nasogastric vs nasojejunal feeding called the Study on Nutrition in Acute Pancreatitis is currently underway, which will provide further evi dence on this subject.…”
Section: Feedingmentioning
confidence: 99%
“…Several RCTs conducted in adults confirmed that nasogastric feeding is equivalent to the nasojejunal route with regard to complications and clinical course [82][83][84][85][86][87] . Two RCTs with smaller sample size group showed that nasogastric feeding is applicable and safe 86,87 .…”
Section: Ap-v33 Should We Choose Nasojejunal or Nasogastric Tube Fmentioning
confidence: 99%
“…Thirty-three articles (21 articles containing patients suffering from SAP as well as 12 articles with MAP patients) were selected. They contained two nonrandomized and 31 randomized controlled clinical trials (Table 2) [16][17][18][19][20][21][22][23][24][25][26][27]29,[31][32][33][34][35][36][37][38][39][40][41][42][43][44][45][46][47][48][49][50]. Finally, statistical analyses were performed on data from articles where both EN and NPO groups were presented, the trial was randomized, and the relevant data were available.…”
Section: Inclusions and Exclusionsmentioning
confidence: 99%